2014
DOI: 10.1074/jbc.m113.514786
|View full text |Cite
|
Sign up to set email alerts
|

Homo-oligomerization of the Activating Natural Killer Cell Receptor NKp30 Ectodomain Increases Its Binding Affinity for Cellular Ligands

Abstract: Background:Immunosurveillance of cancer and infections by natural killer (NK) cells depends on the receptor NKp30. Results: NKp30 forms homo-oligomers for high affinity binding to B7-H6 on malignantly transformed cells. Conclusion: NKp30-dependent signaling of NK cells is increased by homo-oligomerization via its ectodomain. Significance: This is the first study on NKp30 clustering to strengthen the NK cell-target cell interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…Regardless of the underlying mechanisms of regulation, the association of high B7‐H6 protein expression with high degree of differentiation and that of poor prognosis with high B7‐H6 protein expression seems counterintuitive. As far as we know, B7‐H6, one of the costimulatory signals, has two definite functions: On the one hand, it could bind to trigger NK cell cytotoxicity through natural cytotoxicity receptor NKp30 for immunosurveillance of malignantly transformed cells; on the other hand, it could also impair the antitumor immunity by limiting the T‐cell activity, lead to the immune evasion of the tumor cells, and finally engage in the oncogenesis and associate with the tumor progression . However, the mechanism of the tumorigenesis of B7‐H6 is still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the underlying mechanisms of regulation, the association of high B7‐H6 protein expression with high degree of differentiation and that of poor prognosis with high B7‐H6 protein expression seems counterintuitive. As far as we know, B7‐H6, one of the costimulatory signals, has two definite functions: On the one hand, it could bind to trigger NK cell cytotoxicity through natural cytotoxicity receptor NKp30 for immunosurveillance of malignantly transformed cells; on the other hand, it could also impair the antitumor immunity by limiting the T‐cell activity, lead to the immune evasion of the tumor cells, and finally engage in the oncogenesis and associate with the tumor progression . However, the mechanism of the tumorigenesis of B7‐H6 is still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that the stalk domain of NKp30 increases the affinity for binding of its cognate ligands B7-H6 and BAG-6 (26,27) presumably involving stalk-dependent clustering of NKp30 (28). In the current study we have investigated the contribution of individual amino acids within the stalk domain of NKp30 to ligand binding and formation of a signaling-competent NKp30-CD3 complex.…”
Section: Natural Killer (Nk)mentioning
confidence: 92%
“…Non-equivalent-In a previous study we showed that the stalk domain of NKp30 contributes to ligand binding and represents a functional domain of NKp30 (27,28). Even though NKp30 and NKp46 differ in the number of Ig domains and the sequence and length of their stalk domains, they both signal via CD3 (2) (supplemental Fig.…”
Section: The Stalk Domains Of Nkp30 and Nkp46 Are Functionallymentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced B7H6 expression is found in a range of tumours [93,94], with further up-regulation by radiation, chemotherapy and immunotherapy [95]. NKp30 recognizes B7H6 through the complementarity determining region (CDR)like loops of its Ig variable domain with an affinity of 1000 nM (K D ), whereby homo-oligomerization is believed to enhance avidity [90,93,96,97]. Soluble forms of both B7H6 and BAT3 may be released through the action of metalloproteases, and these can inhibit NK cell activity, accompanied by poorer overall survival [93,[98][99][100][101].…”
Section: Nkp30 and Derived Carsmentioning
confidence: 99%